2014
DOI: 10.1007/s00345-014-1403-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal expression of hyaluronic acid and hyaluronic acid receptors in a porcine small intestinal submucosa-augmented rat bladder regeneration model

Abstract: Introduction Hyaluronic acid (HA), a non-sulfated glycosaminoglycan, is an essential component of the extracellular matrix (ECM). Since HA is involved in many phases of wound healing and may play a key role in tissue repair and regeneration, this study was intended to understand temporal and spatial expression of HA and HA receptors (HARs) during the course of bladder regeneration in rats. Materials and methods Sprague-Dawley rats were subjected to partial cystectomy followed by augmentation with porcine sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The IHC staining was conducted by the OUHSC Stephenson Cancer Center Tissue Pathology Shared Resource facilities using a method similar to published previously (25,30,31). The immunohistochemistry protocol was based on the manufacturer's protocol for the Leica Bond-III™ Polymer Refine Detection system (DS 98000).…”
Section: Immunohistochemistry (Ihc) and Digital Image Analysis For Oatp1b1 And Oatp1b3mentioning
confidence: 99%
“…The IHC staining was conducted by the OUHSC Stephenson Cancer Center Tissue Pathology Shared Resource facilities using a method similar to published previously (25,30,31). The immunohistochemistry protocol was based on the manufacturer's protocol for the Leica Bond-III™ Polymer Refine Detection system (DS 98000).…”
Section: Immunohistochemistry (Ihc) and Digital Image Analysis For Oatp1b1 And Oatp1b3mentioning
confidence: 99%
“…A recent study in a rat bladder regeneration model found that HA deposition in a regenerating bladder after partial cystectomy was required for proper wound healing ( 48 ). CD44 expression also increased as the wound healed, mimicking the deposition pattern of HA.…”
Section: Cd44–ha Signaling and Human Diseasementioning
confidence: 99%
“…Previous studies have implicated that HA was involved in wound healing and tissue regeneration, and endothelial cell proliferation, as well as angiogenesis. HA interacted with HA receptors, including the cluster of CD44, receptor for HA-mediated motility (RHAMM), and Toll-like receptor-4 (TLR-4) to regulate urothelial cell proliferation, differentiation, and migration [63,64]. Transgenic mice with the expression of an antisense CD44 cDNA under the control of the keratin-5 promoter exhibited defective keratinocyte proliferation, indicating that HA receptor CD44 played an important role in the regulation of keratinocyte proliferation in response to extracellular stimuli [65].…”
Section: Discussionmentioning
confidence: 99%